Prediction of the site of the aneurysms in the region of the circle of Willis and the vicinity by CT scan - Hirunpat, S.; Pekanan, P.; Uttamakul, P.; Ruxayos, N. (The ASEAN Journal of Radiology, 2023)
Retrospective study of the proved aneurysms, detected by i.v. contrast CT study in 21 cases, relating with the angiographic and surgical results. The aneurysms were mapped on the "pentagon" which was assumed to represent the circle of Willis. Paramedian anterior pentagon represented the site of anterior communicating artery aneurysm and the opposite posterior paramedian or median area was the site of basilar tip aneurysm. The lateral anterior corner was for the aneurysm of the horizontal portion (rare) of the middle cerebral a. or supraclinoid internal carotid a. The lateral posterior corner would be for aneurysm of the posterior communicating a, or distal internal carotid artery. Most of the aneurysms at the genu of the middle cerebral a. (more common than at the horizontal portion) were outside the petagon and were at the region posterior to the anterior middle cranial fossa. Rarer case of the anterior communicating a. was above the pentagon, seen between the floor of both frontal horns.